Estado democrático de direito e participação política no legislativo federal - Silva, Thais Helena da [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
O trabalho objetiva analisar aspectos do acesso à representação política de alguns grupos que representam as minorias sociais no Congresso Nacional. Os grupos minoritários não estão relacionados necessariamente à sua quantidade numérica, mas à história social que indica déficit de representação real dos seus interesses políticos. O recorte temporal do estudo está restrito às eleiçoes de 2014 e 2018, o qual demonstra o perfil dos políticos eleitos naquele período. A hipótese principal aponta, de certo modo, a permanência de padrões pretétritos inerentes às oligarquias, fator que torna desigual a competição eleitoral dos grupos minoritários no atual cenário político brasileiro.

The work aims to expose the access to political representation of some selected groups that make up the social minorities in the National Congress. When dealing with minority groups, it is understood that there is no need to talk about numerical quantity, but about a historical and social issue of segments that fall short of political interests. The focus of the analysis is the 2014 and 2018 elections in order to demonstrate the profile of the politicians who ran and managed to be elected. The second objective is to demonstrate how the ways of the political game and its oligarch scenario dominated by political elites influence the electoral competition of socially minority groups.
Democratic rule of law and political participation in the federal legislative
Keywords: Representação política; Democracia; Minorias sociais; Legislativo; Political representation; Democracy; Social minorities; Brazilian legislation